Platelet aggregation and TGF-beta(1) plasma levels in pregnant women with preeclampsia - Peraçoli, Maria Terezinha Serrão [UNESP]; Menegon, Fernanda Tereza Ferreira [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Costa, Roberto Antonio de Araújo [UNESP]; Thomazini-Santos, Izolete Aparecida [UNESP]; Peraçoli, José Carlos [UNESP] (Elsevier B.V., 2008)
Objectives: Platelets and transforming growth factor-beta(1) (TGF-beta(1)) are thought to be involved in the pathogenesis of preeclampsia. Our objectives were to determine plasma concentration of TGF-beta(1) in normotensive and preeclamptic women in the third trimester of pregnancy and to evaluate the correlation of TGF-beta(1) plasma levels with platelet count and agonist-induced aggregation capacity.Methods: Thirty-three women with preeclampsia were compared with 36 healthy women with uncomplicated pregnancies. Peripheral venous blood samples were obtained, and TGF-beta(1) plasma levels measured by an enzyme-linked immunoassay. Platelet aggregation was induced by the agonist agents adenosine diphosphate (ADP), collagen and epinephrine, and was determined in platelet-rich plasma by aggregometry.Results: Plasma concentrations of active TGF-beta(1) were significantly higher in preeclamptic women (10.41 +/- 2.07 ng/mL) compared with normotensive pregnant women (7.01 +/- 3.29 ng/mL). Platelet number and platelet agonist-induced aggregation percent were significantly lower in patients with precclampsia than in healthy pregnant women. A significant correlation was observed between TGF-beta(1) plasma levels and platelet agonist-induced aggregation percent as between plasma levels of TGF-beta(1) and platelet number in preeclamptic patients.Conclusion: The association between impairment in platelet responsiveness and higher levels of TGF-beta(1) in the plasma of patients with preeclampsia suggests that this cytokine may play a role in the pathophysiological events of preeclampsia that are dependent on platelet activation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Platelets; TGF-beta(1); Preeclampsia; Pregnancy